RANCANGAN PENERAPAN SAK EMKM DENGAN APLIKASI AKUNTANSI UKM PADA BODY GYM FITNESS CENTER MALANG - Sentosa, Getar Dana; Zuraidah, Zuraidah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
SAK EMKM is the financial accounting standards for an entity that classified as MSMEs and to facilitate business owners to prepare financial statements. One of the MSMEs is the Body Gym Fitness Center located in Sawojajar of Malang City is still recording transactions in the form of daily reports and monthly reports. The solution that is expected in the preparation of financial statements is the existence of software that allows MSMEs owners to compile financial statements even if they do not understand accounting. The research method used is descriptive qualitative. The research site is the Body Gym Fitness Center addressed at H7/D27 Danau Jonge Street, Sawojajar, Malang. Research subjects are the manager and cashier of the fitness center. Observations, interviews, and documentations are used as data collection techniques. Data reduction, data presentation, and conclusion drawing are used as data analysis methods.The results of this research are: income statement and balance sheet statement. Notes on financial statements are still compiled in manual way. There are two obstacles faced by the Body Gym Fitness Center to compile the financial statements: a) lack of understanding on financial Reporting, b) the absence of human resources who able to compile financial statements according to SAK EMKM.Â